Fresno County Bar Associations' 105th Annual Bar Banquet - Watkins, Howard::::::::: (1987)
Leonard Zins receiving a plaque of appreciation from Fresno County Bar Association President Herbert Levy Recognized Leonard Zin's 3 years of service on the Fresno County Bar Association Board of Directors